Balanço e evolução temporal de teores de fósforo e potássio no solo em áreas manejadas com agricultura de precisão - Montiel, Luis Ramiro Samaniego (2011)
The need for improving nutrient use efficiency and increase savings demand a better knowledge of soils and production systems. The objective of this study was to evaluate the soil P and K budget and its relationships with their temporal evolution on site-specific management areas. The experiments were carried out in four cropland areas from the Medium Plateau region of the Rio Grande do Sul state, located at the cities of Almirante Tamandaré do Sul, Tio Hugo, Não-Me-Toque and Vitor Graeff. Soil tests were used to verify the spatial variability, budget and temporal evolution of soil P and K levels by the comparison of the years of 2005 and 2009. Regression analysis was performed by the software JMP IN v.3.2.1 to evaluate the relationship between P and K budget and the temporal evolution of soil P and K levels. Cropland areas showed high spatial variability for P and K soil test levels at the beginning of the study, which was decreased by applying precision farming techniques. Relationships between P and K budget and the temporal evolution of soil P and K test levels were positive with the exception of the Vitor Graeff area which showed negative P and K budget. P and K fertilization were 30 and 25% higher in relation to their exportation, respectively. On average, soybean extracted 44 kg P2O5 ha-1 and 63 kg K2O ha-1, while the maize exported 78,5 kg P2O5 ha-1 and 59 kg K2O ha-1. Temporal evolution of soil P and K test levels was high when P and K budget was low and there was a low temporal evolution when the P and K budget was high. On the average of the four cropland areas there were necessary the input of 12,0 kg P2O5 ha-1 to increase 1 mg dm-3 of soil P test levels and the input of 4,1 kg K2O ha-1 to increase 1 mg dm-3 of soil K test levels.